2013
DOI: 10.1542/peds.2013-1073
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning HIV-Infected Youth Into Adult Health Care

Abstract: With advances in antiretroviral therapy, most HIV-infected children survive into adulthood. Optimal health care for these youth includes a formal plan for the transition of care from primary and/or subspecialty pediatric/adolescent/family medicine health care providers (medical home) to adult health care provider(s). Successful transition involves the early engagement and participation of the youth and his or her family with the pediatric medical home and adult health care teams in developing a formal plan. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 23 publications
0
46
1
Order By: Relevance
“…During the HT1 programme some youth reported communication problems with their caretakers regarding their HIV care. Thus, we felt it was important to engage caretakers in the HT2 programme to help them understand factors important in the transition from paediatric to adult HIV care services and to provide an opportunity to improve communication in the family [3,6,23]. We found that youth whose parents had died had lower knowledge scores at 18 months compared to those whose parents were alive.…”
Section: Resultsmentioning
confidence: 99%
“…During the HT1 programme some youth reported communication problems with their caretakers regarding their HIV care. Thus, we felt it was important to engage caretakers in the HT2 programme to help them understand factors important in the transition from paediatric to adult HIV care services and to provide an opportunity to improve communication in the family [3,6,23]. We found that youth whose parents had died had lower knowledge scores at 18 months compared to those whose parents were alive.…”
Section: Resultsmentioning
confidence: 99%
“…20,21 One important barrier to linkage and engagement in care is the dearth of HIV-specialty care specifically geared toward adolescent developmental needs and the lack of seamless transition procedures to adult-based health care. 22 YLHIV must navigate traditional adolescent development issues with the added burden of living with a highly stigmatized illness while not yet having fully developed the internal and social resources to deal with these complex and often competing demands.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, the transition from pediatric to adult health care of adolescents and young adults (AYA) with a variety of chronic health conditions has garnered increasing attention (Baldassano et al, 2002; COMMITTEE ON PEDIATRIC AIDS, 2013; Crowley, Wolfe, Lock, & McKee, 2011; DeBaun & Telfair, 2012; Freyer, 2010; Jurasek, Ray, & Quigley, 2010; Peters & Laffel, 2011; Prior, McManus, White, & Davidson, 2014; J. Reiss & Gibson, 2002; Sable et al, 2011; Tuchman, Schwartz, Sawicki, & Britto, 2010).…”
Section: Introductionmentioning
confidence: 99%